Multiscale Molecular Dynamics Simulations of Polaritonic Chemistry - Luk, Hoi Ling; Feist, Johannes; Toppari, J Jussi; Groenhof, Gerrit (Journal of chemical theory and computation, 2017)
When photoactive molecules interact strongly with confined light modes as found in plasmonic structures or optical cavities, new hybrid light-matter states can form, the so-called polaritons. These polaritons are coherent superpositions (in the quantum mechanical sense) of excitations of the molecules and of the cavity photon or surface plasmon. Recent experimental and theoretical works suggest that access to these polaritons in cavities could provide a totally new and attractive paradigm for controlling chemical reactions that falls in between traditional chemical catalysis and coherent laser control. However, designing cavity parameters to control chemistry requires a theoretical model with which the effect of the light-matter coupling on the molecular dynamics can be predicted accurately. Here we present a multiscale quantum mechanics/molecular mechanics (QM/MM) molecular dynamics simulation model for photoactive molecules that are strongly coupled to confined light in optical cavities or surface plasmons. Using this model we have performed simulations with up to 1600 Rhodamine molecules in a cavity. The results of these simulations reveal that the contributions of the molecules to the polariton are time-dependent due to thermal fluctuations that break symmetry. Furthermore, the simulations suggest that in addition to the cavity quality factor, also the Stokes shift and number of molecules control the lifetime of the polariton. Because large numbers of molecules interacting with confined light can now be simulated in atomic detail, we anticipate that our method will lead to a better understanding of the effects of strong coupling on chemical reactivity. Ultimately the method may even be used to systematically design cavities to control photochemistry.